O nível de satisfação do consumidor turista no Centro de Atenção ao Turista na cidade de Quaraí-RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The present work has the theme Tourism, in relation to the frontier space between Quaraí-RS and Artigas-ROU, this one is focused in the Center of Attention to the Tourist in the Brazilian municipality. This research has as main objective, the identification of the tourist satisfaction level in relation to an information center in the city of Quaraí-RS. Based on the theoretical framework, a quantitative questionnaire was applied to these tourists. From the analysis of the results, it was verified that the overall satisfaction was very good, but we managed to identify some problems, and for them we elaborated strategies for their best performance for the Information Center. This research was important, not only to consider all the aspects that have to be improved, but also because tourism is more competitive each year, it can have practical support such as qualification and possible investments to meet the needs of people who travel.
The level of tourist consumer satisfaction in the Tourism Attention Center in the city of Quaraí-RS
Keywords: Turismo; Centro de atenção ao turista; Informações turísticas; Tourism; Center of attention to the tourist; Tourist information; CNPQ::CIENCIAS SOCIAIS APLICADAS